Survey of Dental Students' Knowledge Levels Regarding Gingival Pigmentation and Smoking Behavior - Fidyawati, Desy; Wicaksono, Adrianus; Mellynia (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Background: Aesthetics is an important aspect in the world of dentistry, and patients have high expectations for aesthetics to increase their self-confidence. Smokers have a high risk for periodontal disease, and smoking causes several abnormalities in the oral cavity, such as pigmentation of the oral cavity, which interferes with the aesthetics of the teeth. Good ability and knowledge are required to identify aesthetic needs. This need can be met by dental graduates. This study aims to determine the level of knowledge of clinical students at FKG UPDM (B) regarding gingival pigmentation to smoking behavior. Material and Methods: This study employs a descriptive research design with a cross-sectional approach. Questionnaires with 10 research questions were distributed online to clinical students at FKG UPDM(B). Results and Discussion: Based on 100 professional students, consisting of 76 female students in the dental profession (76%) and male students in the dental profession 24 people (24%). This study shows that the knowledge of professional students at FKG UPDM (B), all respondents have good knowledge (89.0%). Conclusion: This study shows that the knowledge of research subjects who are professional students at FKG UPDM (B) in general is in a good category (80%-89%)